Yield-limiting nutrient response of lowbush blueberry grown in recent and ancient alluvial soils of the Mekong Delta - Ngoc,Ngo Phuong; Ly,Le Minh; Thao,Pham Thi Phuong (PeerJ, 2024)
Background Blueberries are ornamental plants grown in pots in many yards in the Mekong Delta (MD) region. In this region, the recent alluvial (RA) soil is fertile and ancient alluvial (AA) soil is considered degraded because it only has around a quarter of the nutrient content of the RA soil. Both soils have a high clay content, so organic matter is needed to improve their physical condition. This study aimed to identify the nutrients that limit the yield of blueberries in RA and AA soils of the MD. Methods The pot experiment was performed using a factorial randomized block design (RBD) with two factors: (a) two soil types (RA and AA) and (b) four omission or treatment conditions (NPK, PK, NK, and NP). The same fertilizer formula was used for all treatments, including 45N–20P2O5–20K2O and mixing CHC (10 tha-1) into the potting soil. Results The blueberry yield in AA soil was only 81% of that in RA soil. In both RA and AA soils, N omission caused foliar N content deficiency (10.42 g kg−1), resulting in the content of foliar P (0.84 g kg−1) and K (3.78 g kg−1) to fall below the Trevett threshold. In both RA and AA, N omission resulted in reduced fruit yield (47% and 39%, respectively) as well as reduced weight of the stem (70% and 42%, respectively) and leaf (59% and 46%, respectively). Increased crop yields in soils were mainly related to nitrogen fertilizer. The indigenous nutrient supply (INS) of RA, which is fertile, was high but its apparent nutrient recovery efficiency (ARE) index was low, whereas the INS of AA, or the level of degraded soil, was low but its ARE index was high. In alluvial soils, the higher the INS level, the less positive the impact on the ARE index. In AA soil, the indigenous N and K supplies can be improved through fertilizer investment; however, a balance must be achieved considering economic efficiency.
Keywords: Nutrient response; Blueberry; Ancient alluvial soils; Recent alluvial soils; Mekong delta